Erectile Dysfunction (ED) within Hospital Facilities in Cotonou.. - Natchagande, Gilles; AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; Yevi, Inès Dodji Magloire; Agounkpe, Michel Michael; Kaka, Mahamane Adama Salissou; Sossa, Jean; Hodonou, Detondji Fred; Jacquet, Djamal; SOUMANOU, FOUAD; Hounnasso, Prince Pascal (My University, 2017)
Introduction: Erectile dysfunction (ED) is defined as the persistent inability to achieve the necessary degree of erection for sexual activity. It is a common disease which can significantly affect the quality of life of sufferer and their partners. The purpose of this study is to give an overview of the magnitude of this medical condition in Benin society. Material and Method: It was a multicenter cross-sectional descriptive and analytical study conducted over a period of one month from 1st to 30th June 2015. A questionnaire was prepared for this purpose. Outcomes: The average age in this series is 48.32 with extremes ranging from 18 to 95 years. These patients were predominantly public servants. All our patients (100% of the study population) responded to the single question of John. B. Mckinlay. The global ED prevalence was 52.6%. The multivariate analysis helped to identify a correlation with several factors associated with ED. These factors included: age, occupation, lifestyle, etc. 41.91% of patients with ED and/or other sexual disorders declared “not at all acceptable” to continue living with these disorders. The patients benefitted from different treatments including IPDE-5 and traditional treatment in respectively 32.8% and 40.1% of cases. Conclusion: ED is a condition in its own which has an impact on the patients’ quality of life. Its discovery may lead to the diagnosis of cardiovascular, hormonal or neurological diseases.
Keywords: ED; Sexual Disorder; Sexuality